2017
DOI: 10.1007/s00244-017-0477-7
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Concentrations in Roadside Dust Along Two National Highways in Northern Vietnam and the Health-Risk Implication

Abstract: There is a need to assess the risk of exposure to metals via roadside dust in Vietnam where many people live along the road/highways and are constantly exposed to roadside dust. In this study, we collected dust samples at 55 locations along two major Highways in north-east Vietnam, which passed through different land use areas. Samples were sieved into three different particle sizes and analyzed for concentrations of eight metals using a X-ray fluorescence instrument. The concentrations and environmental indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…There have been number of studies analyzing the particulate matter pollution in Vietnam [20][21][22]. PM 10 and the trace metals bounded with PM 10 have been previously researched in Hanoi [19,23] and Ho Chi Minh [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been number of studies analyzing the particulate matter pollution in Vietnam [20][21][22]. PM 10 and the trace metals bounded with PM 10 have been previously researched in Hanoi [19,23] and Ho Chi Minh [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no investigation on characterization of PM 10 and its chemical compositions at road sites in Bac Giang province. According to our best knowledge, only [13,24] reported the level of metal contamination in street dust in Hanoi and roadside dust along the highways in the North of Vietnam [20,21]. These studies showed that the high concentration of metals in dust observed from downtown area and the high traffic density.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal elements are harmful environmental pollutants with characteristics of high toxicity, concealment, persistent existence, and bio-accumulation [4,5]. Pollution of urban surface dust with heavy metals is a serious environmental issue when it poses a threat to the human health and urban ecoenvironment [6,7]. Through the circulation and migration among various ecosystems, heavy metals accumulating in surface dust can be resuspended in the atmosphere or flushed into the surrounding water system and ultimately cause potential risks [8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out on heavy metals in surface dusts in super cities or towns all over the word in recent decades, whose spatial distribution patterns [11], source identification [12], ecological risk assessment [13], and health risk assessment [5] were conducted. Some researches focused on the dusts on the urban roads [1] and national highways [6]. Some other researches reported the pollution risks of heavy metals in surface dust from urban living areas [14], shops [15], bus stations [16], urban parks [17], schools [3,18], different functional urban areas [19], driving schools [20], and gas stations [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study, the risk of exposure to metals via roadside dust in Hanoi, Vietnam was assessed. It was concluded that the risk of exposure to heavy metals though roadside dust is much higher for children than for adults (356,357).…”
Section: Further Studiesmentioning
confidence: 99%